Post-millennial gothic comedy, romance and the rise of happy gothic - Spooner, Catherine 1974- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
Surveying the widespread appropriations of the Gothic in contemporary literature and culture, 'Post-Millennial Gothic' shows contemporary Gothic is often romantic, funny and celebratory. Reading a wide range of popular texts, from Stephenie Meyer's 'Twilight' series through Tim Burton's Gothic film adaptations of 'Sweeney Todd', 'Alice in Wonderland' and 'Dark Shadows', to the appearance of Gothic in fashion, advertising and television, Catherine Spooner argues that conventional academic and media accounts of Gothic culture have overlooked this celebratory strain of 'Happy Gothic'.